PERGANTIAN CEO, PENGHINDARAN PAJAK, KOMPENSASI EKSEKUTIF DAN MANAJEMEN LABA STUDI KAUSALITAS PADA PERUSAHAAN MANUFAKTUR INDONESIA - natasya putri; Wida Fadhilia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
This study aims to examine the influence of CEO turnover, tax avoidance and executive compensation on earnings management by using discretionary accruals as a proxy of earnings management. The samples of this research were the manufacturing firms listed in BEI (Indonesia Stock Exchange) between 2011 and 2015. The samples were selected by using purposive sampling on 24 companies with 120 observations. The Data were collected from annual report and data analyzed by multiple regression analysis. The results of this study shows that CEO turnover has influence on earnings management, tax avoidance has influence on earnings management, and executive compensation has no influence on earnings management.